Semi-Conducting: Rambles Through the Post-Cagean Thicket - Collins, Nicolas 1954- (New York Bloomsbury Academic, 2025)
"Written by a composer long immersed in new and experimental music this book provides a tour of the music, technologies and people that have transformed how we make, hear and think about sound over the past fifty years. As both a participant and critical observer in the post-Cagean musical landscape, Nicolas Collins uses anecdotes and analysis to survey the history and aesthetics of the musical avant-garde. It follows a personal chronology of observations and experiences with music, technology, economics and culture"-- Provided by publisher
A Hidden Switch -- I am Sitting in a Classroom -- Worlds of Music -- Four Ridiculously Large Speakers -- Interlude : Multitrack -- Playing with Chips -- The Infinite Amplification of Silence (or I Ching for Dummies) -- Old Guard Avant Garde -- Newcastle to Narvik -- The Eden Before Apple -- A Bright Red Electric Guitar -- Interlude : 33 1/3 -- Devil's Music -- Planes, Trains and Step-Down Transformers -- A Computer Walks into a Bar -- We Were All Seated Around the Campfire -- Interlude : Soundcheck -- Still Lives -- STEIM -- IRCAM with a Human Face -- Interlude : Silence -- Whistling in the Woods -- Strange Heaven -- Art School -- Interlude : How Things Work -- Hardware Hacking -- Salvage -- The Missing Switch -- Interlude : Things I'd Like to Own -- Surprise Me
Keywords: Avant-garde; Popular music; Composing; Improvisation; Technology